OPTIMALISASI PERKEMBANGAN MOTORIK HALUS ANAK USIA DINI MELALUI TEKNIK MOZAIK - Dinah Halilah; Lizza Suzanti (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2022)
This study examines the fine motor development of children using the mosaic technique. The purpose of this study was to find out how to optimize children's fine motor development with the mosaic technique. This research method uses a qualitative descriptive approach with two research subjects. Data collection techniques in this study using observation and documentation. Analysis of the data used in this study using data collection, data reduction, data display and affirmation of conclusions. This study shows how children attach origami paper that already has a pattern with a small shape and glue HVS paper which has an apple-shaped pattern in training eye and hand coordination simultaneously. Based on the results of the data in this study, two subjects had optimal fine motor skills using the mosaic technique.